2000
DOI: 10.1073/pnas.250277297
|View full text |Cite
|
Sign up to set email alerts
|

A PPxY motif within the VP40 protein of Ebola virus interacts physically and functionally with a ubiquitin ligase: Implications for filovirus budding

Abstract: VP40, the putative matrix protein of both Ebola and Marburg viruses, possesses a conserved proline-rich motif (PY motif) at its N terminus. We demonstrate that the VP40 protein can mediate its own release from mammalian cells, and that the PY motif is important for this self-exocytosis (budding) function. In addition, we used Western-ligand blotting to demonstrate that the PY motif of VP40 can mediate interactions with specific cellular proteins that have type I WW-domains, including the mammalian ubiquitin li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
473
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 423 publications
(502 citation statements)
references
References 53 publications
26
473
2
1
Order By: Relevance
“…Filovirus RNA synthesis is reliant on NP, VP35, VP30 and L working in a complex 89,90 ; however, during the process, VP24 has been shown to be closely associated with intracellular centres of virus replication, known as inclusion bodies, and has been shown to be required for nucleocapsid and genome packaging [91][92][93] . VP40 directly interacts with cellular endosomal trafficking elements and is key for viral budding 94 . GP requires post-translational modifications in the endoplasmic reticulum and Golgi processes and hence follows a different trafficking pathway to the plasma membrane than do the other viral proteins [95][96][97] .…”
mentioning
confidence: 99%
“…Filovirus RNA synthesis is reliant on NP, VP35, VP30 and L working in a complex 89,90 ; however, during the process, VP24 has been shown to be closely associated with intracellular centres of virus replication, known as inclusion bodies, and has been shown to be required for nucleocapsid and genome packaging [91][92][93] . VP40 directly interacts with cellular endosomal trafficking elements and is key for viral budding 94 . GP requires post-translational modifications in the endoplasmic reticulum and Golgi processes and hence follows a different trafficking pathway to the plasma membrane than do the other viral proteins [95][96][97] .…”
mentioning
confidence: 99%
“…Recent studies have revealed that viral matrix proteins play critical roles during the later stages of virus budding in many enveloped RNA viruses, including retroviruses, rhabdoviruses, filoviruses and orthomyxoviruses; these viral proteins possess a so-called late (L)-domain containing PT/SAP, PPXY and YXXL, which are critical motifs for efficient budding (Bouamr et al, 2003;Ciancanelli & Basler, 2006;Göttlinger et al, 1991;Harty et al, 1999Harty et al, , 2000Wirblich et al, 2006). The PTAP motif was first identified in HIV Gag and has been reported to bind to Tsg101, which functions in vacuolar protein sorting (Garrus et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…NP, viral protein (VP)35, VP30, and L, the RNA-dependent RNA polymerase, are components of the nucleocapsid and are essential for viral replication and transcription (5). VP40 is the matrix protein and is critical for viral budding (18,19). VP24 is essential for the formation of nucleocapsids composed of NP, VP35, and viral RNA (20).…”
mentioning
confidence: 99%